Tadeusz Semadeni (1902–1944). Polski sportowiec, działacz i dziennikarz sportowy, bojownik antyhitlerowskiego ruchu oporu - Uljasz, Adrian (Przegląd Nauk Historycznych, 2015)
Tadeusz Semadeni was a sportsman and sports journalist, one of the creators of water sports in Poland, a propagator of women’s sports. He was one of the founders of the Academic Sports Association (AZS) in Warsaw and the Polish Swimming Association. He was a lawyer by profession – a judge and a prosecutor. The time which was crucial for his development as a columnist was the be-ginning of his career as a journalist in the years 1923–1924, connected with the ‘Stadion’ weekly issued in Warsaw. In 1936 he went to the Summer Olympics in Berlin as the head of the team of Polish swimmers. Under the Nazi occupation, he was the co-founder of the clandestine organi-sation ‘Znak’. He was an activist of the Armed Confederation and the Labour Party. He acted as a judge of the Union of Armed Struggle (ZWZ) and the Home Army (AK). During the Warsaw Uprising he judged and sentenced Germans, Volksdeutsche and other collaborators. He died in the Warsaw Uprising